2012
DOI: 10.1186/1756-6649-12-3
|View full text |Cite
|
Sign up to set email alerts
|

The study of radiosensitivity in left handed compared to right handed healthy women

Abstract: BackgroundRadiosensitivity is an inheriting trait that mainly depends on genetic factors. it is well known in similar dose of ionizing radiation and identical biological characteristics 9–10 percent of normal population have higher radiation response. Some reports indicate that distribution of breast cancer, immune diseases including autoimmune diseases as example lupus, Myasthenia Gravies and even the rate of allergy are more frequent in left handed individuals compared to right handed individuals. The main g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Since in our study all samples have Rh+, we cannot evaluate the association between Rh and radiosensitivity. Another study by Khosravifarsani et al in 2012 showed that radiosensitivity of lefthanders is higher compared to right-handers in healthy female samples [32]. Unfortunately, in this study, we did not evaluate whether the samples are left or right handers.…”
Section: Association Between Blood Group and Radiosensitivitymentioning
confidence: 78%
“…Since in our study all samples have Rh+, we cannot evaluate the association between Rh and radiosensitivity. Another study by Khosravifarsani et al in 2012 showed that radiosensitivity of lefthanders is higher compared to right-handers in healthy female samples [32]. Unfortunately, in this study, we did not evaluate whether the samples are left or right handers.…”
Section: Association Between Blood Group and Radiosensitivitymentioning
confidence: 78%
“…Fritschi et al have stated that workers dealing with pesticides such as Diazinon are at risk of lymphoma cancer especially non-Hodgkin [5]. The effects of radiation on CBMN assay scores were also proved by many studies [6].…”
Section: Discussionmentioning
confidence: 98%
“…The CBMN assay is a standard technique for evaluation of chemical materials and ionizing radiation effects on the DNA. In-vitro CBMN assay was used for measuring the differences in radiosensitivity and DNA damage in different studies [20][21][22]. In this assay, DNA damage could be scored by different indices, including micronuclei, nucleoplasmic bridges, and nuclear buds within binucleated cells [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation